2020
DOI: 10.21203/rs.3.rs-36951/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibacterial wound dressing nanofibrous mats composed of cellulose acetate loaded with chitosan/erythromycin nanoparticles

Abstract: This study attempts to fabricate the antibacterial nanofibrous mats composed of cellulose acetate (CA) nanofibers loaded with erythromycin-chitosan nanoparticles (Ery-CS NPs) intended for infected wound dressing. The Ery-loaded CS NPs were prepared by ionic gelation process and then incorporated into the CA electrospun nanofibers (NFs). The characterization of the NPs and mats were investigated by using dynamic light scattering (DLS), scanning electron microscopy (SEM), Attenuated Total Reflection Fourier tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…[ 131,132 ] The usual dose of topical Ert is reported about 20 mg g −1 . [ 133 ] Ert is known as an antibacterial agent and is often used for gram‐positive bacterial infections. It first inhibits protein synthesis by binding to the 23S bacterial ribosomal RNA molecule in the 50S subunit.…”
Section: Drugs In Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 131,132 ] The usual dose of topical Ert is reported about 20 mg g −1 . [ 133 ] Ert is known as an antibacterial agent and is often used for gram‐positive bacterial infections. It first inhibits protein synthesis by binding to the 23S bacterial ribosomal RNA molecule in the 50S subunit.…”
Section: Drugs In Wound Healingmentioning
confidence: 99%
“…The results showed that these prepared nanofibers have good antibacterial activity against gram‐positive and gram‐negative bacteria and on the other hand, no cytotoxicity was observed on fibroblast cells. [ 133 ]…”
Section: Drugs In Wound Healingmentioning
confidence: 99%
“…Doostanet alexplored the antibacterial potential of a medium spectrum antibiotic, erythromycin, for infected wound care management. A cellulose acetate nanofibrous mat incorporated with erythromycin loaded chitosan nanoparticles was evaluated against E. coli, S. aureusand P. aeruginosa bacterial strains as potential dressing for infected wounds [11]. A recent study reported an increase in poor solubility of curcumin via encapsulation into a saline-hydrogel nanoparticulatevector.…”
Section: Wound Care Management Via Nano Formulationsmentioning
confidence: 99%
“…For example, the hybrid nanofibers can be fabricated by directly blending the target NPs with the polymer solution for electrospinning, [ 29 ] sol‐gel emulsification method for wrapping the NPs within the fiber, [ 30 ] layer by layer stacking, [ 8 ] in situ growth or coating of NPs on the nanofibers surface. [ 31 ] The NPs in electrospun fibers hybrid composites display a broad application potency ranging from wound dressings with antimicrobial and/or angiogenesis bioactivities, [ 32 ] osteogenesis [ 33 ] and periosteal regeneration, [ 34 ] anti‐tumor treatment, [ 35 ] biosensing [ 36 ] and gene delivery [ 9 ] (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%